Dramatic Earthly Paradise: An Architectural Concept of the Resort Hotel in Mandalika, Lombok - Kurniawan, Febri Wahyu; Ardhiati, Yuke; Anggita, Diptya (Journal of Aesthetics, Creativity and Art Management, 2024)
Mandalika Special Economic Zones in Lombok, West Nusa Tenggara, Indonesia, is experiencing dynamics after the Covid-19 pandemic, in the form of updating the 2015 and 2018 master plans, including the accommodation design concept. This study was carried out based on qualitative methods aimed at producing the design of a resort hotel in Mandalika Area in Lombok. This architectural study is a qualitative research that refers to the studies of Linda Groat and David Wang. Based on the research results, a hotel resort concept with the theme of the Dramatic Earthly Paradise was obtained. The 'earthly paradise' reflects the beauty of the island of Lombok (natural panorama of beaches, mountains and culture) into an integrated design. The benefit obtained from this study is as an inspiration for fulfilling tourism accommodation in resort areas based on a combination of local wisdom and universal design.